A SET/MYND chromatin re-modelling protein regulates Dictyostelium prespore patterning - NUÑEZ-CORCUERA, BEATRIZ (2011)
SmdA is a Dictyostelium orthologue of the SET/MYND chromatin re-modelling proteins. In developing structures derived from a null mutant for smdA (a smdA- strain), prestalk patterning is normal, but using a prespore lacZ reporter fusion, there is ectopic accumulation of β-galactosidase in the prestalk region. As wild type slugs migrate, there is continual forward movement and re-differentiation of prespore cells into prestalk cells. Thus, a potential explanation for the ectopic reporter localization in smdA null prestalk cells is an increased rate of re-differentiation and anterior movement of prespore cells. In support of this notion, analysis of an unstable lacZ reporter, driven by the prespore promoter, reveals a normal staining pattern in the smdA- strain. We suggest that one or more genes regulated by SmdA acts to repress prespore re-specification.